ANALISIS PENGELOLAAN SAMPAH DI TPA GRIYO MULYO DALAM PRESPEKTIF INTEGRATED SUSTAINABLE WASTE MANAGEMENT - Putri Febri Anggraeni; Oktarizka Reviandani (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Effective urban waste management is a fundamental pillar in achieving Sustainable Development Goals (SDGs) Goal 11 regarding sustainable cities and communities. As the second-largest waste contributor in East Java, Sidoarjo Regency faces a critical challenge at the Griyo Mulyo Landfill, which is experiencing a capacity crisis with waste piles reaching 15 meters despite undergoing modern technological rehabilitation. This study aims to analyze waste management at the landfill through the lens of the Integrated Sustainable Waste Management (ISWM) model. Utilizing a qualitative descriptive method with the interactive data analysis model by Miles, Huberman, and Saldana, data were gathered through observations and in-depth interviews with informants from the Sidoarjo Environmental Agency (DLHK) and landfill management. The results indicate that Griyo Mulyo Landfill has systematically integrated the three primary dimensions of ISWM. In the stakeholder dimension, a decentralized role distribution has been established between regulators and operators, alongside active involvement from surrounding village communities. In the technical dimension, the system has transformed into an integrated flow encompassing sorting, composting, and residue landfilling, supported by SIPPAS digital technology. Regarding supporting aspects, the Regional Public Service Agency (BLUD) status provides managerial flexibility, further bolstered by the